Corrigendum to “Transition toward a fully renewable-based energy system in Chile by 2050 across power, heat, transport and desalination sectors” - Osorio-Aravena, Juan Carlos (International Journal of Sustainable Energy Planning and Management, 2020)
This is a corrigendum to the article Transition toward a fully renewable-based energy system in Chile by 2050 across power, heat, transport and desalination sectors published by the International Journal of Sustainable Energy Planning and Management with DOI: http://doi.org/10.5278/ijsepm.3385